Experimental and numerical investigations of double bracket to CHS column joints - Ahmed H. Abdelaal; Tamer H. Radwan; Amr A. Shaat (Scientific Reports)
Abstract The primary objective of this study is to precisely characterize the behavior of double bracket-to-circular Hollow Section (CHS) column joints due to combined internal forces resulting from double tensile loading in opposite directions. In order to accomplish this goal, an experimental program consisting of eight test specimens has been carried out and numerical finite element modeling has been employed for the same specimens to analyze the stresses and deformations that occur within the vicinity of bracket-to-CHS joints. A total of 15 finite element models were constructed to simulate the initial study, addressing boundary conditions and facilitating verification and results comparison. The study included an investigation of various parameters, including the spacing between brackets in the longitudinal direction, as well as the depth-to-thickness ratio of the CHS columns and adding a T-stiffener to the bracket configuration. The study determined that an increase in the diameter-to-thickness ratio of the CHS columns significantly reduced the overall strength of the joint. Furthermore, findings suggested that increasing the longitudinal spacing between brackets resulted in an increase in single-bracket joint strength and a minor reduction regarding joint strength considering the effect of line loading. Moreover, adding a T-stiffener shape for the brackets enhanced the joint strength and prevented bracket tip fracture. In addition, a distinct behavior arises when considering joints with positive eccentricity, where the forces’ line of action extends beyond the circular cross-section of the CHS. In such cases, a reduction in joint strength is observed. Finally, a modification factor “A” is applied to the X-type branch plate-to-CHS strength equation presented by the AISC360-22 to account for the longitudinal spacing between brackets.